Biocidal activity of Ba2+-doped CeO2 NPs against Streptococcus mutans and Staphylococcus aureus bacterial strains. Issue 49 (15th September 2021) - Sisubalan, Natarajan; Karthikeyan, Chandrasekaran; Senthil Kumar, Venugopal; Varaprasad, Kokkarachedu; Haja Hameed, Abdulrahman Syed ahamed; Vanajothi, Ramar; Sadiku, Rotimi
Abstract : The highest antibacterial activity was achieved for Ba-doped CeO2 (BCO) NMs and is suitable for healthcare applications. Abstract : Mishandling of antibiotics often leads to the development of multiple drug resistance (MDR) among microbes, resulting in the failure of infection treatments and putting human health at great risk. As a response, unique nanomaterials with superior bioactivity must be developed to combat bacterial infections. Herein, CeO2 -based nanomaterials (NMs) were synthesized by employing cerium(iii ) nitrate and selective alkaline ions. Moreover, the influence of alkaline ions on CeO2 was investigated, and their characteristics, viz. : biochemical, structural, and optical properties, were altered. The size of nano Ba-doped CeO2 (BCO) was ∼2.3 nm, relatively smaller than other NMs and the antibacterial potential of CeO2, Mg-doped CeO2 (MCO), Ca-doped CeO2 (CCO), Sr-doped CeO2 (SCO), and Ba-doped CeO2 (BCO) NMs against Streptococcus mutans ( S. mutans ) and Staphylococcus aureus ( S. aureus ) strains was assessed. BCO outperformed all NMs in terms of antibacterial efficacy. In addition, achieving the enhanced bioactivity of BCO due to reduced particle size facilitated the easy penetration into the bacterial membrane and the presence of a sizeable interfacial surface. In this study, the minimum quantity of BCO required to achieve the complete inhibition of bacteria was determined to be 1000 μg mL −1 and 1500 μg mL −1 for S. mutans and S. aureus, respectively. The cytotoxicity test with L929 fibroblast cells demonstrated that BCO was less toxic to healthy cells. Furthermore, BCO did not show any toxicity and cell morphological changes in the L929 fibroblast cells, which is similar to the control cell morphology. Overall, the results suggest that nano BCO can be used in biomedical applications, which can potentially help improve human health conditions.